Dealloying of Quasi-High Entropy Alloys: Fabrication of Porous Noble Metals/Metal Oxides - Ziying Meng; Jun Zhou; Chunling Qin; Zhifeng Wang (Metals)
High entropy alloys (HEAs) have been widely studied due to their special crystal structure, but their bulk structure and low specific surface area limit their further application in broader fields. In this work, the dealloying of precious metal Cu35Pd35Ni25Ag5 quasi-HEAs is performed. Porous noble metals with micro prism array structure and porous noble metal PdO/Ag2O/NiO oxides with nano “ligament/pore” structure are obtained by constant potential dealloying and free dealloying, respectively. In this way, the porosification of quasi-HEAs and noble metal oxides is achieved. Moreover, the effects of dealloying parameters on pore morphology and phase structure of dealloyed materials are studied, and the evolution mechanisms of pore structures of different dealloying products are discussed. The work provides strategies for the preparation of porous precious metal quasi-HEAs and porous noble metal oxides by the dealloying method. These products present great potential for application as functional materials in hot fields such as catalysis and energy storage.